METHODOLOGY OF MEASUREMENT THE HUMAN CAPITAL - A. Dorofeev (Вестник университета)
This paper proposes a methodological approach to the measurement of human capital on the basis of the life cycle model. The algorithm of the measurement of human capital using the Verhulst equation.